An X-band GaNHEMT power amplifier design using an artificial neural network modeling technique - Lee, SY; Cetiner, BA; Torpi, H; Cai, SJ; Li, J; Alt, K; Chen, YL; Wen, CP; Wang, KL; Itoh, T (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2001)
In this paper, the first gallium nitride (GaN) based high electron mobility transistor (HEMT) power amplifier design using an artificial neural network (ANN) modeling technique is presented. The ANN technique was used to model the small signal behavior of a device with a gate periphery of 1 mm and a gate length of 1 mum over the broad frequency range from 1 GHz to 26 GHz with multiple bias points, based on fitting calculated S-parameters to measured S-parameters. A single stage amplifier constructed using these parameters showed a gain of about 7 dB and an output power of 1.2 W at 8 GHz when biased at V-ds = 20 V and I-ds = 220 mA in class AB mode. The good agreement between measured and simulated results was shown in both S-parameter modeling and in amplifier design.
Keywords: device modeling; gallium nitride (GaN); HEMT; neural network technique; power amplifier; DEVICES; Engineering; Physics